Medeni usul hukukunda dava malzemesinin taraflarca getirilmesi ilkesi - Pehlivan, Ali (My University, 2003)
Dava malzemesinin taraflarca getirilmesi ilkesi; davanın temelini oluşturan vakıaların ve bunların gerçekleşip gerçekleşmediği yolunda ikame edilecek delillerin yargılamaya kural olarak ancak taraflarca getirilebileceğini; hakimin kendiliğinden; yani taraflarca getirilmeyen bir vakıayı nazara alamayacağını, delil ikame edemeyeceğini, taraflarca üstünde uzlaşılan vakıaların kural olarak hakimi bağlayacağını ifade etmektedir. Bu ilkenin temelinde özel hukukta geçerli olan irade özgürlüğü ve maddi hukuktan Medeni Usul Hukuku'na yansıyan tasarruf ilkesi bulunmaktadır. Madem ki bireyler, irade özgürlüğü ve tasarruf yetkisini haizdir, dava malzemesi davanın taraflarınca getirilmelidir. Bu, Medeni Usul Hukuku'nun amacı olan maddi gerçeğe ulaşılması bakımından yerindedir; çünkü bir uyuşmazlıkla ilgili bulunan taraflar bu uyuşmazlığı en iyi bilecek durumdadır. İkinci olarak her bir taraf, yargılamada kendi menfaati savunmak için lehine olabilecek bütün vakıa ve delileri yargılamaya getirecektir. Türk Medeni Usul Hukuku açısından bu ilkenin temeli; HUMK 75. m. 1. f.'dır. Hakim, taraflarca ileri sürülmeyen bir vakıayı nazara alamayacak; hatta bu yönde bir hatırlatmada dahi bulunamayacaktır. Ancak HUMK, maddi gerçeğe ulaşılması bakımından bu ilkenin mutlak şekliyle uygulanmasını öngörmemiş ve kimi istisnaları kabul ederek ilkeyi tamamlamaya çalışmıştır: 75. m. 2. f. vakıalar ve 3. f. deliler yönünden hakimin soru sorma hakkı veya işaret etme veya aydınlatma ödevi olarak adlandırılan yetki ve ödevidir. Hakim, taraflarca yargılamaya getirilen vakıalarla sınırlı olmak üzere; şüpheli veya çelişkili gördüğü hususlar konusunda tarafların bilgisine başvurabilir, delil ikame etmelerini talep edebilir. İkincisi HUMK'ta doğrudan düzenlenmeyen; ancak MK 2. m.'deki dürüstlük kuralından çıkarılan doğruluk ödevidir; dava malzemesi getirilirken taraflar; doğruluk ve özenle davranmalı, yalan beyanda bulunmamalıdır. The principal of the removal of the documents above the case by its sides; tells that the facts which present the basic of the case and the evidences which prove the real situation about the case may be taken to the court only by the sides of the case; that the judge may not presume after the facts which are not told by the sides and may not create new evidences above the case, and that the judge is limited by the facts which are already spoken by the both sides. At the basic of this principal stands the freedom of will which is current also in the civil law and the power of disposal which is reflected to the Law of Civil Procedure from the material law. As a result of the fact that the individuals possess the power of disposal, they should have also the possibility to remove the documents above the case. This is pertinent with the aim of the Law Of Civil Procedure which is to catch the concrete reality; because firstly the sides of the case are much more closer to the facts above the conflict than the other subjects of the procedure. Secondly, each side would be able to bring to the court the documents in its advantage in the aim of using them as a defense. After the Turkish Civil Procedure, this principal is coded in the 1st paragraph of the article 75 of the Code Of Civil Procedure. The judge may not consider a fact which is not told by one of the sides, and may even not remind a clue in this way. But The Turkish Code of Civil Procedure doesn't show the way of an absolute practice about the article and determine some exceptions which complete the principal: By the article 75 the judge is charged with questioning and clarifying the facts (in the 2nd paragraph) and the evidences (in the 3rd paragraph) above the case. The judge who still is limited by the facts brought by the sides; may have some information about the points which are not clear and doubtful and may ask for some more evidences. The second exception which is not coded clearly in the Code of Civil Procedure; but which is told in the second article of the Civil Code is duty to tell the truth. The sides who remove the documents above the case should act with honesty and care and shouldn't use false documents.
Keywords: Evlilik; Hukuk; Medeni Hukuk; Özel hukuk